Approaching National Christianities in the Nordic Region - Boije, Erika (A journal of church and state, 2025)
This article introduces "national Christianities" as an approach to explore the persistent, yet changeable, historical and contemporary intersections of nationalism and Christianity by focusing on the Nordic region. The article challenges tendencies in nationalism studies to view the nation as a phenomenon replacing religion during the nineteenth and twentieth centuries. It also problematizes the idea of secularization and the diminished influence of Christianity across the Nordic countries. By doing so, the article highlights that Christianity has played a significant role in constructing ideas and ideals of the Nordic region as well as mobilizing national identities since the emergence of romantic nationalism in the nineteenth century. It demonstrates that the intersections of Christianity and nationalism offer an imperative lens for understanding Nordic nations and societies, both in their historical trajectories and contemporary developments.